2012
DOI: 10.1111/j.1469-8129.2011.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration and ethnic nationalism: Anglophone exit and the ‘decolonisation’ of Québec

Abstract: This article explains the effects of ethnic nationalism on Anglophone and Francophone migration. The rise of Québec ethnic nationalism in the 1960s dismantled the cultural division of labour, which created new opportunities for Francophones but threatened Anglophones' traditional dominance over the Québec economy. This had negative consequences for Anglophones but positive outcomes for Francophones, which in turn accounts for differences in migration patterns. Drawing from the internal colony model as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
0
8
0
1
Order By: Relevance
“…Considering the declining influence of the Anglophone minority in Quebec, studies showed that QA out-migration was an exit strategy motivated in part by political helplessness (Pettinicchio, 2012). Interviews with QAs who left the province revealed that many did not feel accepted by the Francophone majority, especially in the workplace (Magnan, 2004).…”
Section: Internal Migration In Canadamentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the declining influence of the Anglophone minority in Quebec, studies showed that QA out-migration was an exit strategy motivated in part by political helplessness (Pettinicchio, 2012). Interviews with QAs who left the province revealed that many did not feel accepted by the Francophone majority, especially in the workplace (Magnan, 2004).…”
Section: Internal Migration In Canadamentioning
confidence: 99%
“…Future studies could also focus on the age-old problem of vulnerable minorities who are confronted with the risk of staying too long in their region of origin at the possible cost of suffering collectively at the hand of intolerant factions of the dominant majority. The option of "voting with one's feet" by emigrating may be salutary not only in the case of international migration but also in cases of internal migration within divided nations (Pettinicchio, 2012). Willingness to leave one's ancestral territory as an exit option can be seen as another barometer of intergroup tensions complementing other indicators such as assimilation within the dominant mainstream, separatism, intergroup competition, and intergroup conflict (Tajfel & Turner, 1986).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…The exit option in the form of "white flight" -the unwillingness of white people to remain in neighborhoods where a growing non-white population approaches a critical tipping point -has been studied extensively in US and European contexts (Schelling 1972;Krysan 2002;Pais, South, and Crowder 2009;Kaufmann andHarris 2014, 2015). Others have studied out-migration from the perspective of "internal colonialism" (Hechter 1975) -as with the Anglophone exit from Québec (Pettinicchio 2012).…”
Section: Nationalist Rhetoric and Fear-induced Migrationmentioning
confidence: 99%
“…Pettinicchio (2012) insiste sur le rôle du rendement économique relatif de la migration en tant que déterminant des décisions des anglophones et des francophones à cet effet.…”
Section: Présentation Les Anglophones Au Québecunclassified